Simulation Study of Sand Removal Device for Geothermal Well Recharge Water - Zhu, Jiayu (International Journal of Natural Resources and Environmental Studies, 2024)
Geothermal well recharge water is a study to protect the environment and conserve resources, while recharge water containing sand will produce clogging, the experiment is conducted by simulating the separation efficiency with different precision and time, combining the three-stage treatment process of sand removal-coarse filtration-fine filtration based on a metal wire mesh cartridge, and applying the Reynolds turbulence model of the algebraic stress model, the control equation of the flow of the airflow (k-ε) model and Reynolds stress model are considered together. The conclusion drawn from the combined considerations is that the filter media used is a wire mesh filter media, and the wellhead sand can be completely removed by three-stage filtration.